Do groups fight more? Experimental evidence on conflict initiation - Changxia Ke; Florian Morath; Sophia Seelos (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
This paper investigates whether distributional conflicts become more likely when groups are involved in the fight. We present results from a laboratory experiment in which two parties can appropriate resources via a contest or, alternatively, take an outside option. Keeping monetary gains expected from fighting constant across all treatments, the experiment compares conflict choices of players in two-against-two, one-against-one, and two-against-one settings. Overall, we find evidence for a higher propensity to opt for conflict when entering the fight in a group than when having to fight as a single player. The effects are strongest in endogenously maintained groups and in the presence of group size advantages (i.e., in two-against-one). The results can be explained by a stronger non-monetary utility from fighting in (endogenous) groups and coincide with a biased perception of the fighting strength in asymmetric conflict.
Keywords: C92; D70; D72; D74; D91; 330; Conflict; contest; conflict resolution; group decision-making; group identity; alliance; experiment